Implementasi Program Budaya Bersih dan Kreativitas Mahasiswi Ilmu Kesejahteraan Sosial Universitas Sumatera Utara dalam Pengelolaan Sampah Botol Minuman di Panti Asuhan Penuh Pengharapan - Simatupang, Wulan Purnama Sari; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
The implementation of the "Clean Culture and Creativity Program by Social Welfare Students at the University of North Sumatra" aims to address the issue of managing beverage bottle waste at the Full Hope Orphanage. In this context, Social Welfare students play an active role in program implementation, utilizing their knowledge and skills to promote sustainable cleanliness practices and waste management. Through a participatory and creative approach, the program aims to enhance environmental awareness, empower the community, and mitigate the negative impacts of plastic waste on the environment. Implementation methods include education, training, and practical activities at the orphanage. It is hoped that this program will make a positive contribution to creating a cleaner, healthier, and more sustainable environment at the orphanage and serve as inspiration for similar efforts elsewhere.